BIOSYSTEMATIC STUDIES ON COTUGNIA ORIENTALIS SP. NOV. (CESTODA: DAVAINEIDAE, FUHRMANN 1907) FROM GALLUS GALLUS DOMESTICUS - SANJAY SHAMRAO NANWARE,; R.M. DHONDGE,; D. B. BHURE, (The Bioscan, 2011)
The present investigation deals with a new species of the genus Cotugnia, Dimare 1893 from the intestine of Gallus gallus domesticus at Loha, District – Nanded (M. S.) India. The new species Cotugnia orientalis come closer to all the known species of the genus Cotugnia in general topography of organ but differs due to having scolex quadrangular, suckers four, placed at four comers and muscular, Rostellar hooks 115 – 125 in numbers, arranged in a single circle, mature proglottids broader than long, tests oval to rounded 45-50 in numbers, cirrus poucy cylindrical, cirrus short, contained within cirrus pouch, vas deference long tube, genital pore marginal, vagina posterior to the cirrus pouch, ovary bilobed, ‘W’ shaped, gravid proglottids broader than long, egg capsules 50-60 in numbers and having 6-7 eggs in each capsule.